2016
DOI: 10.1016/j.joad.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Pathological research on acute hepatic and renal tissue damage in Wistar rats induced by cocoa

Abstract: A B S T R A C TObjective: To ascertain the functional integrity of renal and hepatic tissues of Wistar rats fed with processed cocoa bean-based beverages and raw cocoa bean products-containing diets by using biochemical and histological methods. Methods: Thirty Wistar rats were designated on the basis of experimental diets which were given for 28 days. At the end of the feeding period, blood samples were drawn, and renal and hepatic tissues were excised from the experimental rat groups for functional tests and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…The rapidity with which urea and creatinine are cleared from circulation and excreted in the urine is a diagnostic parameter for ascertaining renal tissue functionality. The present study conformed to previous reports, in which streptozotocin-induced diabetic rats and Wistar rats fed with unprocessed cocoa exhibited marginal elevation of serum creatinine concentration but with marked elevation of serum urea concentration, which was diagnostic of renal dysfunction [79,80]. However, studies showed that elevated serum creatinine concentration was a more reliable diagnostic biomarker than that of serum urea concentration for renal dysfunction [81].…”
Section: Discussionsupporting
confidence: 92%
“…The rapidity with which urea and creatinine are cleared from circulation and excreted in the urine is a diagnostic parameter for ascertaining renal tissue functionality. The present study conformed to previous reports, in which streptozotocin-induced diabetic rats and Wistar rats fed with unprocessed cocoa exhibited marginal elevation of serum creatinine concentration but with marked elevation of serum urea concentration, which was diagnostic of renal dysfunction [79,80]. However, studies showed that elevated serum creatinine concentration was a more reliable diagnostic biomarker than that of serum urea concentration for renal dysfunction [81].…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the histopathological status of the liver, photomicrograph sections of renal tissues (Figure 7) showed that the distortions in renal tissue architecture correlated with the levels of alterations in their blood indicators; serum creatinine and urea concentrations as previously described. 60 Furthermore, the tissue architecture of fibrotic rats administered with raw and hydrothermal processed herbs confirmed the limited capacities of the herbs to ameliorate renal dysfunction within the experimental period of 28 days.…”
Section: Discussionmentioning
confidence: 73%
“…15,60 Autopsy samples of the renal and hepatic tissues of the different animal groups, fixed in 10% formolsaline (pH = 7.2) for 24 h and washed with continuous flow of distilled water. The specimens were cleared in xylene embedded in paraffin in hot air oven at 56°C for 24 h. Paraffin bees wax tissue blocks were prepared for sectioning at 4-mm thickness using a semi-automated rotatory microtome.…”
Section: Hepatorenal Tissue Histopathological Examinationsmentioning
confidence: 99%